Effectiveness of digital-based mathematics learning media on sequence and series material - Andy Ahmad; Abdul Hakim Maruf; Chrisnaji Banindra Yudha (Nashir Al-Kutub Indonesia, 2024)
One of the mathematical topics closely related to real-life problems is sequences and series, which are used to model and predict various phenomena and patterns. This material helps enhance students' abilities in applying mathematical formulas accurately in everyday contexts. The aim of this study is to examine the effectiveness of digital-based learning media in supporting students' understanding of sequences and series. A simple descriptive quantitative method was employed, focusing on evaluating the media's effectiveness through basic statistical analysis. The results indicate that digital-based learning media are effective in facilitating students’ comprehension of sequences and series material. These findings suggest that such media can be utilized in mathematics instruction to improve learning outcomes. However, further research is needed to evaluate the efficiency of this approach in broader learning contexts and to explore how it can be integrated with other instructional media to enhance students' overall academic performance. The implication of this research is that teachers should consider incorporating digital tools to complement traditional methods in teaching mathematical concepts. Additionally, curriculum developers are encouraged to design interactive and accessible digital content that aligns with students’ learning needs and technological habits.